Gender Taboos and Homophobia in Unoma Azuah’s Embracing My Shadow: Growing Up Lesbian in Nigeria. - Dogoh, Karen S.; Nwiyi, Joy I. (The Gender Truth Journal, 2025)
In sexual politics, queer is a concept that describes atypical sexual preferences and descriptive of a minority that do not subscribe to the conventional gender heterosexual identity. The Nigerian society like many other heteronormative societies is fixated in its delineation and acceptance of sexuality and gender. Non-conformity by anyone to the same means can subject you to any form of homophobia. Nigeria has a queer community. However, legislation in Nigeria still prohibits homosexual relations, prescribing as much as fourteen years imprisonment as punishment for this in Nigeria’s Criminal Code Act. With diverse calls for the respect of human rights across the globe, Nigeria and Africa at large still cringes at the knowledge of a queer identity and treat same as socio-culturally alien. Thus, this paper examines the emergent concept of queer in Nigerian literature and the relationship between queerness and selfhood in Embracing My Shadow: Growing up Lesbian in Nigeria using the Queer theory. The study finds that, Unoma Azuah’s portrayal of queer characters in her memoir and Unoma’s several attempts at asserting her queerness as a personal identity is consistent with ongoing agitation for LGBTQ rights. It argues that Azuah’s narrative is contextualised within a social space with structures that challenge queer as an emerging norm of being. The paper has therefore argued that Nigeria’s queer literature and the possibility of queer’s search for selfhood and domesticity in Nigeria is characterised by taboos and limits that attest to the complexity of the society and its espoused sexual norms.